Investigating user intention on usage frequency of e-wallet in Vietnam - Tran, Thi Minh Anh (2020)
Nowadays, E-wallet, a new payment gateway, has gained its popularity in e-commerce and retail market. This study investigates factors impacting user intention on E-wallet usage frequency in Vietnam